Destination sequenced distance vector routing taking into account signal to noise for flying ad hoc network - Vo Thanh Tu; Binh, Le Huu; Phan Dinh Nguyen Vu (Vietnam Journal of Science and Technology, 2023)
Flying ad hoc network (FANET) is becoming more popular in both military and civilian applications. The primary characteristic of the FANET is high mobility, which results in a constantly changing topology. This is a significant challenge for protocols that control data transmission from nodes to base stations. As a result, many research groups have recently been attracted to the study of data transmission control protocols in FANET, typically routing protocols. This paper presents the application of the Destination Sequenced Distance Vector (DSDV) routing protocols for FANET. We improve the DSDV routing protocol by considering signal-to-noise ratio (SNR) when discovering new routes. The simulation results show that the improved DSDV algorithm outperforms the traditional DSDV algorithm in terms of network throughput, end-to-end delay and SNR.